Evaluasi Perencanaan Jembatan Beton Bertulang Balok T dengan Variasi Mutu Antara K-200 – K-300 - Sumantri, Devie Arisandy; Bayzoni, Bayzoni; Sebayang, Surya (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Design of reinforced concrete T beams bridge with variation concrete strength is conducted to determine design of a bridge which can be built in remote area with a minimum concrete quality but still in accordance with the applicable safety standards. The bridge has a span of 15 m, a width of traffic lanes 2 x 5.5 m with variations concrete strength of K-200, K-225, K-250, K-275 and K-300. The calculations that have been done show that in cross section 2-2 , cross section 3-3 and cross section 4-4, the lower concrete strength will obtains more flexural girder reinforcement needs. However at cross section 1-1 the amount of reinforcement on every concrete strength has the same amount of reinforcement because the reinforcement ratio is the ratio of minimum reinforcement. Shear reinforcement of girder using the same diameter will produce the reinforcement needs with larger spacing while concrete strength increased. Maximum girder deflection that occurs will be smaller if the concrete strength increases. However, if the amount of reinforcement in the quality of K-200 more larger then the value deflection will be smaller compared with the quality of K-300. The lower quality of flexural strength concrete slab with the D16 will get smaller reinforcement spacing.Key word : bridge, T beams, quality variation, Upper structure